Investigations into friction, film thickness and heat generation of water-based lubricants containing nanoparticles, surfactant and dispersant in hydrodynamic journal bearing - Azizan, M.A.H.; Mohd Fadhli, Nur Hidayatul Ezzaty; Kamarudin, Muhammad Adam; Idrus, Muhammad Faris; Sulaiman, Mohd Hafis (Malaysian Tribology Society, 2024)
Water-based lubrication offers superior cooling capacity compared to traditional oil-based lubrication. This study aims to evaluate the heat generation between sliding surfaces and the subsequent friction reduction using Water-based Lubricants (WBL) containing ceramic and carbon nanoparticles in hydrodynamic journal bearings. The nanoparticles used in this investigation include Magnesium Oxide (MgO), Silicon Carbide (SiC), a mixture of Magnesium Oxide and Silicon Carbide (MgO/SiC), Aluminium Oxide (Al2O3), and treated Graphene Oxide (tGO). The experiments were conducted on a TM 282 journal bearing test rig, with rotational speeds ranging from 200 to 1,200 rev/min, and under two different constant contact normal load settings of 10N and 15N. The methodology involved determining the minimum film thickness and constructing Stribeck's curve. The results demonstrate that heat generation remained low in all test WBLs due to the excellent cooling capacity of water, facilitating efficient heat dissipation and temperature reduction. Among the tested nanoparticles, tGO proved particularly effective in creating a complete separation between the rotating shaft and bearing surfaces, resulting in the highest film thickness and, consequently, a significant reduction in friction.